Jegos treniruotes poveikis raumenu strukturai: apžvalga - Mirzayev, J. (Sporto Mokslas-Sport Science, 2017)
Muscle architecture is among the most important factors that determine the function of muscles. Muscle architecture is the "organizer" of muscle fibres in muscle strength generating relative line and includes several important aspects: 1) normalized fibre length, 2) pennation angle, and 3) physiological cross-sectional area. Architectural changes in muscles immediately respond to resistance training, but it is not entirely dependent on muscle contraction mode. To the date, we very poorly understand architectural parameters for each muscle; thus, further studies are needed to explore the architecture of individual muscles and further to expand our understanding of this important organizer of muscle fibres. The purpose of the article is to examine the relationship between strength training and muscle structures. Method chosen: analysis of scientific literature. Results and conclusions. In general, contemporary scientific research confirms in the 80-ies identified circumstantial evidence in favour of muscle architecture changes with the help of strength training. Hypertrophy of the muscle increases the angles of pennate muscles. The more muscle hypertrophy evolves, the less specific voltage occurs. Increased muscle volume in the eccentric training is closely related to increasing length of the beams, but pennation angle is not changed. The level of tension is responsible for the change in maximal voluntary contraction. Strength training is needed to formation of skeletal muscles, increase of strength and quality of muscles as well as for muscle morphology in the elderly. Architectural changes in the muscles immediately respond to weight training, but it is absolutely independent from muscle contraction mode. Age significantly affects the architecture of human muscles, and aging leads to negative structural changes of muscle function. Further long-term studies should be conducted to determine exactly, what structures are responsible for the increase in knee range of motion for static stretching.